2011
DOI: 10.1038/nrmicro2540
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the effects of the environment and host genotype on the gut microbiome

Abstract: To what extent do host genetics control the composition of the gut microbiome? Studies comparing the gut microbiota in human twins and across inbred mouse lines have yielded inconsistent answers to this question. However, candidate gene approaches, in which one gene is deleted or added to a model host organism, show that a single host gene can have a tremendous effect on the diversity and population structure of the gut microbiota. Now, quantitative genetics is emerging as a highly promising approach that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
1,064
3
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,318 publications
(1,115 citation statements)
references
References 119 publications
38
1,064
3
10
Order By: Relevance
“…The GI tract of animals is one of the most complex microbial ecosystems on Earth, and it is continuously affected by factors associated with the host (Spor et al 2011, Van den Abbeele et al 2011 and the outside environment (Claesson et al 2012). This complexity has been an obstacle to study single independent factors associated with its changes over time and among different populations of animals (e.g., healthy and diseased).…”
Section: The Gi Microbiotamentioning
confidence: 99%
“…The GI tract of animals is one of the most complex microbial ecosystems on Earth, and it is continuously affected by factors associated with the host (Spor et al 2011, Van den Abbeele et al 2011 and the outside environment (Claesson et al 2012). This complexity has been an obstacle to study single independent factors associated with its changes over time and among different populations of animals (e.g., healthy and diseased).…”
Section: The Gi Microbiotamentioning
confidence: 99%
“…Distinct community structure and composition characterizes different vertebrate and invertebrate species in their natural environments, global microbiota and interspecies relatedness, reflecting host phylogeny and incorporating elements of developmental and nutritional specialization (Ley et al, 2008a, b;Ochman et al, 2010;Yidirim et al, 2010). Such complex interactions between deterministic (genetic and developmental), environmental and stochastic factors in the assembly and dynamics of vertebrate gut microbiota are being studied intensely, from fundamental ecological perspectives to its impact on host health and disease (Dethlefsen et al, 2006;Ley et al, 2006;Dethlefsen et al, 2007;Palmer et al, 2007;Ley et al, 2008a;Turnbaugh et al, 2009;Reid et al, 2011;Spor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Significant advances in understanding the individual roles of host and environmental factors on the composition of vertebrate gut microbiota have resulted from studies on genetically inbred mouse lines (reviewed in Spor et al (2011)). Such studies have used both conventionally reared and germ-free animals inoculated selectively with different bacterial isolates or natural microbiota samples.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of microbes residing in the human body, especially in the gut, outnumbers that of human cells [3]. A vast array of recent studies has identified many microbial enterotypes in the human gut [4], [5], [6], [7], [8], [9], [10] and their potential roles in immunity [5], [7], [8], development [8], digestion [9], and other functions [10].…”
Section: Introductionmentioning
confidence: 99%